Psikophoria Untuk Remaja Rehabilitasi Narkoba di Sumatera Utara - Neni Triastuti (Cattleya Darmaya Fortuna, 2022)
There is a need for life skills in a social rehabilitation center for victims of narcotics, psychotropic and other addictive substances abuse, which so far have only been able to depend on third party funding sources. Victims of abuse of narcotics, psychotropics and other addictive substances are victims who have come close to even consuming narcotics, psychotropics and other addictive substances that are destroying the nation's generation. Drugs (narcotics, psychotropics and other addictive substances) can endanger human life, if consumed with inappropriate way, can even cause death (1) Drugs have a very broad negative impact; both physically, psychologically, economically, socially, culturally, defense and security, and so on (2).. Another Victim Social Rehabilitation Center